Presupposition Used by The Characters in Uncharted Movie - Putra, I Gede Ngurah Priyatna Oka; Rajeg, Gede Primahadi Wijaya; Mulyana, Novita (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to identify the types of presupposition and reveal the meaning of each presupposition found in the Uncharted movie. The data for this study was taken from the dialogs spoken by the characters in the Uncharted movie. In this study, the qualitative research method was used to analyze the data. This study applied Yule’s (1996) presupposition theory and supported by the theory of meaning by Thomas (1995). The results showed that all of the six types of presupposition were found in the characters’ utterances from the Uncharted movie. These six types were existential presupposition, factive presupposition, lexical presupposition, structural presupposition, non factive presupposition, and counterfactual presupposition. The analysis also revealed a variety of meanings of all the presuppositions found, where each of the meaning was influenced by the contextual aspects when the utterance is spoken; this made every meaning of the presupposition uttered by the speaker can be understood by the interlocutor by observing the context of the utterance. This study enhances the comprehension of how presupposition is used in conversation and its impact on listeners’ interpretation.